Konsep Desain Lapangan Puputan Klungkung sebagai Taman Rekreasi - Balconis, Anak Agung Trinanda Benczad; Semarajaya, Cokorda Gede Alit; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap, 2022)
The design concept of Lapangan Puputan Klungkung as a recreational park. Public space is an inseparable part of a city. Lapangan Puputan Klungkung is one of the public spaces in the city center of Klungkung Regency that provides sports and recreation facilities for the community. The government plans to organize this public space as a community recreation facility to improve the quality of public recreation spaces. This research aims to produce a representative concept design of public recreation space for local communities. It used the survey method and the data were collected through field observations, interviews, and literature study, and then the collected data were analyzed descriptive qualitatively which refers to the complete design process. The results indicate that the location of this site is very strategic, easy to access, and connected to nearby locations. The design concept used the "Zelfbesturend-landscap" by collaborating history with recreation. It recommends changing the name of Lapangan Puputan Klungkung to Lapangan Puputan Klungkung Ida Dewa Agung Jambe and creating a statue of Ida Dewa Agung Jambe which becomes a focal point or landmark. Lapangan Puputan Klungkung area includes a staging area, a Pancasila stage area, a rare park or children's playground, a yowana park or a sitting area, a lingsir park or a stone path reflection area, a skateboard playing area, a gym area, a photography exhibition area, a food court area, and fountain area with a statue of Ida Dewa Agung Jambe.